2015
DOI: 10.1186/s13046-015-0250-6
|View full text |Cite|
|
Sign up to set email alerts
|

Linc00152 promotes proliferation in gastric cancer through the EGFR-dependent pathway

Abstract: BackgroundLinc00152 has been identified highly associated with the tumorigenesis and development of gastric cancer, however, the detailed mechanism of Linc00152 involved still remains unclear.MethodsRT-PCR and western blot were used to detect the expression of Linc00152 and EGFR. The CCK8 and EDU assay was employed to measure cell proliferation while xenotransplantation technology was applied in BALB/C nude mice. The interaction between lncRNA and target protein was investigated by RNA pull-down and RNA immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
116
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 21 publications
10
116
0
Order By: Relevance
“…We observed that high expression level of EGFR-AS1 in GC patients was significantly correlated with tumor size, but no significant correlation between EGFR-AS1 expression and other clinicopathological features were These data suggest that EGFR-AS1 serves as an oncogenic lncRNA in gastric cancer. The expression of EGFR in clinical samples was found to be significantly higher in GC tissues than in adjacent non-tumor tissues, which is consistent with other reports [31]. Also, a significantly positive correlation was observed between the expression of EGFR and EGFR-AS1.…”
Section: Discussionsupporting
confidence: 81%
“…We observed that high expression level of EGFR-AS1 in GC patients was significantly correlated with tumor size, but no significant correlation between EGFR-AS1 expression and other clinicopathological features were These data suggest that EGFR-AS1 serves as an oncogenic lncRNA in gastric cancer. The expression of EGFR in clinical samples was found to be significantly higher in GC tissues than in adjacent non-tumor tissues, which is consistent with other reports [31]. Also, a significantly positive correlation was observed between the expression of EGFR and EGFR-AS1.…”
Section: Discussionsupporting
confidence: 81%
“…Previously published studies have revealed that the knockdown of linc00152 could inhibit cell proliferation and suppress cell cycle progression [22, 37, 38]. In our study, we obtained similar results to such studies.…”
Section: Discussionsupporting
confidence: 82%
“…As a novel LncRNA, Linc00152 is increased in several cancers and exerts multiple functions to influence the tumor progression. [26][27][28] In this study, we report for the first time that Linc00152 promotes L-OHP resistance in colon cancer cells in vitro and in vivo. Mechanistically, Linc00152 confers resistance to L-OHP by competitively binding miR-193a-3p, upregulating ERBB4, and then inducing the activation of AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 69%